Improving the Speaking Ability of the Students at Public Vocational School 6 Malang, Indonesia, Using Animation Movies as Teaching Media - Prilla Lukis Wediyantoro (Universitas Merdeka Malang, 2016)
This study was a Classroom Action Research which was aimed at improving the speaking ability, particularly in expressing ideas and feelings in English, of the students at Public Vocational School 6 Malang, Indonesia, using animation movies as teaching media. The subjects of this study were thirty five students of the eleventh grade at Public Vocational School 6 in Indonesia. Performance test was employed to measure the students speaking ability. To be successful in using animation movies as media in teaching speaking, the writer used a strategy that involved the following steps: 1) building up the students confidence in speaking English without provided texts, 2) encouraging the students to produce vocabulary orally and vocabulary drilling through picture description activity, 3) enhancing the students grammar mastery as well as fluency in speaking through story completion activity. 4) testing the students speaking performance comprising four aspects: fluency, vocabulary, pronunciation, and structure trough role-play activity. In addition, the subtitle of the animation movies used was Indonesian subtitle and students were allowed to take brief notes during the teaching and learning process.